Designing Vocabulary Materials for English for Theology Course at Sekolah Tinggi Agama Kristen Negeri (STAKN) Toraja Based on Needs Analysis - theo dedi palimbunga' (Teaching English as a Foreign Language Overseas Journal, 2016)
The objectives of the research are as follow: (1) to find out the topics inEnglish for Theology Course that the students need to learn at STAKNToraja and (2) to design the specialized vocabulary materials in each topicthat the students need to learn in English for Theology at STAKN Toraja.This research was conducted at STAKN Toraja. The subjects of thisresearch are the seventh semester students of academic year 2014/2015 andTheological lecturers. The topics and subtopics that need to be learned bythe student in English for Theology Course are: Topics and subtopics:(1)Prayer : Lord’s Prayer (King James Version and Today’s EnglishVersion)and classroom Prayer. (2) the Ten Commandments , (3) the Apostle’sCreed, (4) Holy Bible: Books of the Old Testament and Books of the NewTestament, (5) God: The nature of God and the Attributes of God, (6)Jesus Christ: The person of Christ and The work of Christ (7) HolySpirit:The work of Holy Spirit and The names of Holy Spirit, Man:Thecreation of man and The fall of man, (8) Church: Worship, and Sacrament,(9) Salvation :Repentance and Faith, (10) Last Things:The secondcoming of Christ and Judgement, and (11) The Prophets and The Apostles.